Placental growth factor testing to assess women with suspected pre-eclampsia - Pluddemann, A (BMJ Publishing Group, 2019)
Pre-eclampsia diagnosis is currently made based on clinical signs including blood pressure and proteinuria measurements. A recent trial analysed the use of placental growth factor to assess women with suspected pre-eclampsia.